2001
DOI: 10.1097/00007890-200107150-00022
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Trial of Inhaled Nitric Oxide in Clinical Lung Transplantation

Abstract: Prophylactic-inhaled NO does not prevent RI in human lung transplantation. However, inhaled NO, started at reperfusion, improves gas exchange and reduces pulmonary artery pressure in those patients who develop RI.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
38
0
4

Year Published

2004
2004
2023
2023

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 96 publications
(43 citation statements)
references
References 18 publications
1
38
0
4
Order By: Relevance
“…Careful use of sedation and paralysis, close hemodynamic monitoring, and avoidance of nosocomial pneumonia are important. Nitric oxide has been shown to improve oxygenation, reduce pulmonary artery pressure without affecting systemic pressure, and shorten the duration of mechanical ventilation in case series (Date et al 1996;Ardehali et al 2001). Its primary effect is likely due to improvement in V/Q matching because NO is delivered to alveoli that are ventilated, although NO also has important anti-inflammatory properties related to neutrophil, macrophage, and platelet function (Coggins and Bloch 2007).…”
Section: Postoperative Carementioning
confidence: 99%
“…Careful use of sedation and paralysis, close hemodynamic monitoring, and avoidance of nosocomial pneumonia are important. Nitric oxide has been shown to improve oxygenation, reduce pulmonary artery pressure without affecting systemic pressure, and shorten the duration of mechanical ventilation in case series (Date et al 1996;Ardehali et al 2001). Its primary effect is likely due to improvement in V/Q matching because NO is delivered to alveoli that are ventilated, although NO also has important anti-inflammatory properties related to neutrophil, macrophage, and platelet function (Coggins and Bloch 2007).…”
Section: Postoperative Carementioning
confidence: 99%
“…NO possesses anti-inflammatory properties, and inhaled NO has been shown to attenuate pulmonary I-R injury in preclinical studies [51]. While two uncontrolled clinical studies suggested that inhaled NO may be beneficial in patients who develop lung I-R injury [52,53], a small randomized, placebo-controlled study demonstrated that inhaling NO (20 ppm) commencing 10 min after reperfusion did not affect the physiological or clinical outcome of patients after lung transplantation [54]. Additional studies will be required to define the therapeutic role of inhaled NO in patients who have developed I-R injury after lung transplantation.…”
Section: Treatment Of Pulmonary Ischemia-reperfusion Injurymentioning
confidence: 99%
“…Inhaled NO has been shown to attenuate ischemia-reperfusion injury in the lung and other organs in preclinical 55 and in clinical studies. 56,57 However, a recent randomized, placebo-controlled study demonstrated that inhaling 20 ppm NO beginning 10 minutes after reperfusion does not affect the physiological or clinical outcome of patients after lung transplantation. 58 …”
Section: Inhaled No To Treat Ischemia-reperfusion Injurymentioning
confidence: 99%